Knowing Yet Not Knowing: The Irony of the Evangel in Romans 10 - Eko Nugroho Onggosanusi (Indonesian Journal of Theology, 2014)
Is Romans 10 simply an excursus on the need for evangelism and mission in the midst of Paul’s “doctrine of predestination”? In this article, a chiasm is identified and utilized as a framework to further analyze Romans 10. It is demonstrated that the chiasm lends itself to accentuate the epistemological irony of Israel’s response to the gospel. Despite the glory of the gospel that was proclaimed in the Hebrew Bible, the majority of the Jews in Paul’s time remained in ignorance as they missed the hermeneutical key to understanding the Mosaic Law, namely, “Christ is the goal of the law for righteousness to everyone who believes.” Rather than an excursus within Paul’s doctrinal discourse, Romans 10 is the climax of the irony of Israel as the most privileged people who failed in their hearing and understanding.